Maternal Circulating Exosomal miRNAs as Non-invasive Biomarkers for the Prediction of Fetal Ventricular Septal Defect - Jin, Yuxia; Ai, Ling; Chai, Xiaojun; Tang, Ping; Zhang, Weihua; Yang, Li; Hu, Yue; Xu, Ying; Li, Suping (Frontiers in Genetics, 2021)
Objective: This study aims to discover circulating exosomal miRNAs as potential noninvasive biomarkers early detection of fetus with ventricular septal defect (VSD). Method: A total of 182 pregnant women including 91 VSD cases and 91 matched controls were included in this study. Exosomes were isolated and next-generation sequencing was used to obtain a profile of dysregulated exosomal miRNA. The differential abundance was verified by quantitative real-time PCR (q RT-PCR). . Receiver operating characteristic (ROC) curves were conducted to evaluate the diagnostic accucary Results: 77 serum exosomal miRNA were uncovered to be differentially expressed in the VSD group as compared to the control group. Among these, five down-regulated exosomal miRNA were validated by qRT-PCR. hsa-miR-146a-5p was identified to be capable of distinguishing VSDs from controls (area under the ROC (AUC): 0.997; p < 2.2e-16). Conclusion: circulating exosomal miRNA, in particular, hsa-miR-146a-5pmay be a predictive biomarker for non-invasive prenatal diagnosis of fetal VSDs.